Evaluation of liposomal particle size in different assays (Research, Society and Development, 2023)
Liposomes composed of rice (RL) and soy (SL) lecithins were produced by reverse phase evaporation, using as a solvent for solubilization of rice and soy lecithins the Chloroform P.A. With this, the objective was to perform different assays to evaluate the average size and polydispersity index of liposomes with and without the incorporation of the phenolic compound extracted from Spirulina LEB - 18. The pure liposomes were characterized in size distribution, polydispersity index, and ζ-potential. Liposomes in different assays, on the other hand: A) Liposomes samples with and without phenolic extracts of microalgae were freeze-dried in a freeze-dryer (model LIOB 003, Biosan), were subjected to solubilization in Ultrapure water for characterization. B) Liposome samples with and without phenolic extracts of microalgae were made by centrifugation at 10,000 g for 30 minutes. C) Liposomes samples with and without phenolic extracts of microalgae were submitted to centrifugation at 10,000 g for 30 min and filtration through a membrane filter of 0.22 (Filter For Syringe 0.22 a Kasvi) and 0.45 µm pore size (Membrane Millipore). Then these assays were subjected to size and polydispersity evaluation. Therefore, it was verified that assay C obtained the best sizes. With the results obtained, it is possible to emphasize the role of liposomes as an essential tool for enhancing the antioxidant profile of phenolic extracts of Spirulina sp. LEB-18.